A Scoping Review of Place-based Education in A Context of Environmental Education, Outdoor Education, and History Education - Nor Fauzian Kassim; Mohd Kasri Saidon; Zolkefli Bahador; Muhammad Irfan Zulkifli (Proceeding of International Conference on Multidisciplinary Research, 2024)
This scoping review aims to analyze Place-based Education (PBE) research in the context of Environmental Education (EE), Outdoor Education, and History Education which have been published in peer-reviewed journals in the last twenty years. Researchers map the themes included in this research corpus, highlight EE and other specific subjects such as Outdoor Education and History Education where PBE was analyzed, and categorize the themes that emerged from the research. The Model of PBE dimensions by Ardoin et al. (2012) has been referred to as the main model in this research. Recently, PBE took part as a pedagogical approach that emphasizes the connection between the teaching and learning process. The physical place and nature are the most important elements in PBE. Teachers, students, and the community also play their roles in PBE. It incorporates the meanings and experiences of place in teaching and learning, which can extend beyond the classroom. The purpose of this study is to explore the dimensions of place: A confirmatory factor analysis of data from three ecoregional sites. The implication of the study can be determining the policymakers, administrators, scholars, educators as well as teachers in many countries increasingly seek to integrate PBE as a pedagogical approach into curricula. The findings will help other researchers steer future research on PBE. This research will be a guide for new educational policy and can be the best school practice.